Abstraction and reuse mechanisms in web application models - Rossi, Gustavo Héctor
In this paper we analyze different abstraction and reuse mechanisms that should be used in Web applications to improve their evolution and maintenance. We first review the OOHDM approach for defining a Web application model, in particular the separation of the navigational model from the conceptual model. We next focus on abstraction and composition mechanisms in both models showing how to combine OOHDM’s views with the concept of node aggregation. We introduce navigation and interface patterns and show the way in which patterns generate the architecture of Web design frameworks. We strongly argue that in the currently state of the art of Web applications we can build models of families of similar applications to improvedesign reuse. Next, we present our notation for specifying Web frameworks, giving some examples in the field of E-commerce. Some further work is finally discussed.